Sociodemographic factors determining depression in women aged 15 to 49 - Demographic Survey of Family Health, 2015 - Bautista López, Luis (2020)
The research aimed to determine the sociodemographic factors associated with depression in the population of Peruvian women aged 15 - 49. Being the Family Health Demographic Survey 2015, the database. The research was quantitative, correlational level, non-experimental design. The selection and refinement of the variables was based on the objectives, considering 13763 cases. From this, it was determined that 33.2% of the women suffer from depression whose levels are: 19.4% mild, 7.1% moderate, 3.8% severe and 2.9% very severe. By means of the proportional odds model, the sociodemographic factors associated with depression were determined (p-value<0.05): high school level of the partner, poor and medium wealth level, having suffered violence from their partner, having two or more sexual partners, diagnosis of diabetes or hypertension, having smoked in the last 12 months and having drunk alcohol at some time.